Analisis Kesalahan Peserta Didik dalam Menyelesaikan Soal Matematika pada Fungsi Komposisi dan Fungsi Invers - Alfitrisni Yuliana Kolins; Wahyuningsih Wahyuningsih; Nurfitriah Safrudin; Muhamad Epi Rusdin (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2020)
In learning mathematics, students often experience mistakes or omissions in solving the questions given both the questions of practice, assignments, tests, and exams. This study aims to determine the student's errors mistakes in solving mathematical problems in the composition and inverse functions in SMA Negeri 1 Maumere. The method used is descriptive qualitative, with X MIPA 4 students' research subjects, amounting to 34 people who were selected based on purposive sampling technique where this subject who gets material on compulsory mathematics, namely the material composition function and inverse function. Data collection procedures are taken through the provision of test questions and interviews whit students. Data analysis includes data reduction, data presentation, and conclusions. This study results can be said that the student's errors in solving mathematical problems in the composition and inverse functions of high, medium, and low ability students make the same mistakes, namely errors in using data, language interpretation errors, and technical errors.